The Effect of Debt to Equity Ratio and Total Asset Turnover on Return on Assets with Profit Growth as a Moderating Variable in the Manufacturing Sector Listed on the Indonesia Stock Exchanged - Rachmania Syifa; Maiyaliza (Indonesian Journal of Business Analytics, 2026)
With profit growth acting as a moderating variable, this study attempts to examine the impact of Total Asset Turnover (TATO) and DER on ROA in manufacturing businesses listed on the Indonesia Stock Exchange between 2022 and 2024. Using secondary data from business financial accounts, this study uses a quantitative methodology. Purposive sampling was used to determine the sample, yielding 78 observations. Multiple regression and MRA were used to analyze the data. The findings show that ROA is significantly impacted negatively by DER and positively by TATO. Nevertheless, the association between TATO and DER on ROA cannot be moderated by profit growth, suggesting that asset efficiency and capital structure have a greater impact on profitability.